Natural co-infection of solanum tuberosum crops by the potato yellow vein virus and potyvirus in colombia (2014)
The Potato yellow vein virus (PYVV), a Crinivirus with an RNA tripartite genome, is the causal agent of the potato yellow vein disease, reported in Colombian since 1950, with yield reductions of up to 50%. Co-infection of two or more viruses is common in nature and can be associated with differences in virus accumulation and symptom expression. No evidence of mixed infection between PYVV and other viruses has been reported. In this study, eight plants showing yellowing PYVV symptoms: four Solanum tuberosum Group Phureja (P) and four Group Andigena (A), were collected in Cundinamarca, Colombia to detect mixed infection in the isolates using next generation sequencing (NGS). The Potato virus Y (PVY) complete genome (similar to N strain) and the Potato virus V (PVV) partial genomes were detected using NGS and re-confirmed by RT-PCR. Preliminary field screening in a large sample showed that PYVV and PVY co-infect potato plants with a prevalence of 21% within the P group and 23% within the A group. This is the first report of co-infection of PYVV and potyvirus in Colombia and with the use of NGS. Considering that potyviruses enhance symptom severity and/or yield reductions in mixed infections, our results may be relevant for disease diagnosis, breeding programs and tuber certification.